Assessment of Availability, Teachers’ Proficiency and Challenges of ICT Integration in Teaching Secondary School Mathematics and Science in Bauchi State, Nigeria - P., Dogo,; I.T., Tyoor,; M., Joseph,; E. I., Sulai,; E. I., Sulai,; G., Huseyn,; Y. D., Samaila, (Kashere Journal of Education, 2021)
The study assesses status of integration of Information and Communication Technologies (ICT) in teaching mathematics and science at Public Senior Secondary School in Bauchi Central Educational zone of Bauchi State, Nigeria. The study was aimed to; find out types of available ICT facilities for teaching mathematics and science; establish teacher’s proficiency level of integration of ICT in teaching and learning of Mathematics and Science, and establish challenges faced in the integration of ICT facilities for teaching mathematics and science, Descriptive research design was used for the study. Non Proportional and Purposeful sampling were used for choosing fifty (50) teachers who formed the sample of the study. The sample size was taken from a target population of 250 (20%) mathematics and science teachers. Two instruments were used for data collection. Included were structured and open ended questionnaires and interviews. Data were analyzed using descriptive statistics. Findings revealed high percentage of teacher’s response on the availability of ICT facilities in the study schools, included were white board (74.5 %), laptops (68.6%), printers (56.9%), computer device (50.9%), smart board (50.1 %) and projectors (49.0%). Half (51.0%) of teachers reported internet service and scanning machine not functional. Few teachers (15.7%) reported computers and printers (11.7 %) not functional. Majority (44%) of mathematics and science teachers have a fair knowledge of using ICT facilities to present lesson. Result revealed teachers lack of workshop/seminar on ICT integration (88.2%), students’ ratio to ICT facilities (computers) (86.3%) and lack of time for teachers (58.6%) using ICT during lesson were major challenges. The implication of the study is that effective ICT integration can only be actualized if new initiatives are taken. Thus the study recommended that Mathematics and science teachers should be engaged on professional development training with emphasis on ICT integration in the classroom situation. Stake holders in education sectors and school administrators most ensure effective functions of available ICT facilities in secondary schools